ISTILAH KEKERABATAN PADA MASYARAKAT CINA BENTENG - Sonya Ayu Kumala; RMT Multamia Lauder; Frans Asisi Datang; Winci Firdaus (Balai Bahasa Provinsi Daerah Istimewa Yogyakarta, 2023)
Language as part of our culture refers to both general and specific aspects. Specifically, a language has a distinctive aspect that makes it different from other languages. One of the distinguishing aspects can be seen from the greeting or register in terms of kinship. The term kinship in the discipline of linguistics falls into the scope of sociolinguistics. The term kinship according to Wardaugh (2009) is a characteristic in a language that is generally found in every language. The term kinship is being used to address or refer to other people in relation to ourselves (ego) in a structural system that is connected by blood relations, descent, or the occurrence of marriage. The Chinese Benteng community in Tangerang uses a different and distinctive kinship term compared to the Chinese community in other cities in Indonesia. In general the Benteng Chinese community no longer uses their original language as a whole, but speaks Indonesian with a mix of surrounding languages, namely Sundanese and Javanese. The language of their ancestors is still found used by the older generation, trading activities, traditional rituals, and kinship. In addition to the aspect of language use, other forms of cultural acculturation also can be seen such as in dance, musical instruments, and culinary arts. In general, it can be said, China Benteng has a peculiarity that is still upholding the culture of the ancestors but also absorbs the surrounding culture well. This study aims to describe the terms in the Chinese Benteng kinship system, namely through the classification of kinship terms (Chaer, 1997) and analysis of the language distribution of kinship terms. This study was structured using a qualitative descriptive approach. The interview method was used in extracting information from informants, besides that note-taking techniques were also used to document data mining. The results of the analysis show that the terms of kinship in the Cina Benteng community are grouped into three, namely the terms of direct kinship, indirect kinship, and due to marital relations. The distribution of forming languages or used in Chinese Benteng kinship terms are Chinese, Sundanese, and Javanese.Cina Benteng dan Tangerang menjadi satu kesatuan yaitu sebagai objek dan konteks yang potensial dikaji dari sudut pandang bahasa dan budaya. Cina Benteng dengan kemampuan adaptasi dan akulturasi yang unik serta khas apabila dibandingkan dengan model komunitas Tionghoa lain yang ada di Indonesia. Pada tingkat kebahasaan, istilah kekerabatan menjadi hal yang universal yaitu ditemukan di semua bahasa dan juga sekaligus unik yaitu mencirikan masyarakat pemilik istilah kekerabatan tersebut. Penelitian ini bertujuan untuk mendeskripsikan istilah dalam sistem kekerabatan Cina Benteng yaitu melalui klasifikasi istilah kekerabatan yang dianalisis secara semantis dan analisis bahasa pembentuk istilah kekerabatan. Penelitian ini disusun dengan menggunakan ancangan deskriptif kualitatif. Metode wawancara digunakan dalam menggali informasi dari informan, selain itu juga digunakan teknik catat untuk mendokumentasikan penggalian data. Hasil analisis menunjukan istilah kekerabatan dalam komunitas Cina Benteng dikelompokkan menjadi tiga yaitu istilah kekerabatan langsung, tidak langsung, dan karena hubungan perkawinan. Hasil analisis menunjukan bahwa istilah kekerabatan Cina secara umum masih mengikuti struktur dan sistem kekerabatan seperti Tionghoa pada umumnya di kota lain di Indonesia, misalnya perbedaan sebutan kerabat dari pihak ayah dan ibu. Akan tetapi juga sekaligus menunjuk kekhasan dengan mengkombinasikan istilah kekerabatan tionghoa yang beradaptasi dengan konteks budaya dan bahasa yang bersinggungan. Distribusi bahasa pembentuk atau yang digunakan dalam istilah kekerabatan Cina Benteng adalah bahasa Cina, Indonesia (Melayu), Sunda, dan Jawa.